Central bank communication with the general public - Lena Dräger (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2023)
This paper surveys the literature on the role and effects of central bank communication with the general public, particularly regarding the formation of macroeconomic expectations. It starts by giving a brief overview of the recent "communication revolution" in central bank communication. The challenges for central bank communication with the public are outlined by surveying the evidence about low average knowledge on inflation and monetary policy in the population. Next, I evaluate the effects of direct communication, distinguishing between challenges to getting the attention of the public and effects of information on the public's inflation expectations once attention is gained. Finally, I review the role of the media as transmitter of central bank communication to the public.
Keywords: E52; E58; D84; 330; Central bank communication; consumers; households; literature survey; RCT studies